Multi-disciplinary preliminary design assessments of pusher counter-rotating open rotors for civil aviation - Bellocq, Pablo (Cranfield University, 2012)
As a consequence of fuel cost escalation and increased stringent engine emission regulations, interest in counter-rotating open rotor engines (CRORs) has been renewed. R&D efforts are currently ongoing to develop the technologies required to ensure the appropriate levels of structural integrity, noise, vibrations and reliability. The assessment of the impact of the main low pressure preliminary design and control parameters of CRORs on mission fuel burn, certification noise and emissions is necessary to identify optimum design regions. These assessments aid the development process when compromises need to be performed as a consequence of design, operational or regulatory constraints. These assessments are not possible with the state-of-the-art aero-engine preliminary design simulation tools. Novel 0-D performance models for counter-rotating propellers (CRPs) and differential planetary gearboxes, as well as 1-D and 0-D performance models for counter-rotating turbines (CRTs) were developed and verified using available data. These models were used to create 0-D pusher geared (GOR) and direct drive (DDOR) open rotor engine performance simulation modules allowing the independent definition of the design and operation of each of the two counter-rotating parts of the CRP and CRT. A multi-disciplinary preliminary design simulation framework was built using the novel engine performance modules together with dedicated CROR aircraft performance, engine geometry and weight, gaseous emissions and certification noise simulation modules. Design space exploration and trade-off studies were performed and minimum fuel burn design regions were identified for both the pusher GOR and DDOR. A 160 PAX aircraft flying a business mission of 500 NM was chosen for these studies. Based on the assumptions made, the main conclusions of these studies are as follows. · Fuel burn reductions of ~1-2% are possible through optimised propeller control · The propeller diameter for minimum mission fuel burn lies between 4.26 and 4.7 m · The design nozzle pressure ratio for minimum mission fuel burn lies between 1.55 and 1.6 · CRPs with 13 or 14 blades per propeller provide minimum mission fuel burn · Increasing spacing between the propellers reduces noise significantly (~6 EPNdB for each certification point) with a relatively small fuel burn penalty (~0.3-0.5%) · Relative to unclipped designs, 20% clipped CRPs reduce flyover noise by at least 2.5 EPNdB and approach noise by at least 4.5 EPNdB. The corresponding fuel burn penalty is ~2 % for a GOR and ~3.5% for a DDOR. · Sideline and flyover noise can be reduced by increasing the diameter of the CRP and appropriately controlling CRP rotational speeds. Approach noise can be reduced by either reducing the diameters or the rotational speeds of the propellers. · The rotational speed of the forward propeller for minimum noise is higher than that for minimum mission fuel burn for all the studied CROR designs. · Regardless of clipping, reducing the rotational speed of the rear propeller relative to the forward propeller reduces noise and, to a certain limit, also mission fuel burn. (further reductions in rotational speed would have an adverse effect on fuel burn) · An increase in the number of blades results in an increase in certification noise. The main recommendations for further work are as follows. · Integrating the 1-D CRT model with the 0-D DDOR performance model in order to assess the impact of different CRT design criteria at engine and mission levels · Developing preliminary design methods to account for changes in aircraft weight and aerodynamics due to changes in engine design and required cabin noise treatment.